PENGARUH LINGKUNGAN KERJA, DISIPLIN DAN PELATIHAN TEKNIS TERHADAP KINERJA PEGAWAI TEKNIS DI DINAS ENERGI DAN SUMBER DAYA MINERAL PROVINSI SUMATERA UTARA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Silaban, Pasaman; Panjaitan, Ferry; Situmorang, Bernat (UNIKA Santo Thomas, 2023)
The purpose of this study was to determine the effect of the work environment, discipline and technical training on the performance of technical staff at the Xi Pandan Forest Management Unit Technical Implementation Unit. This research applies descriptive and explanatory methods. Taking into account the relatively small number of members of the population, namely 32 people, all members of the population become the object of research. Thus this research was conducted by census method. Data collection techniques using interviews (intervew), and through distributing a list of questions (questionaire) to respondents. Research data were analyzed using multiple linear regression analysis. The results showed that competence, facilities and training simultaneously had a significant effect on performance in the Xi Pandan Region Forest Management Unit Technical Implementation Unit, competence and facilities partially had a positive and significant effect on performance while training partially had a positive and insignificant effect on performance in the Unit Technical Executor of the Xi Pandan Region Forest Management Unit. Performance variations can be explained by variations in competence, facilities and training of 86.4%